Space exploration - Szymanski, Jennifer (New York, NY : Children's Press, an imprint of Scholastic Inc., 2022)
This book introduces young readers to math concepts around space exploration.
School Library Journal, November 2021
Includes index.
K-3
650L
Keywords: Mathematics -- Juvenile literature; Space sciences -- Mathematics -- Juvenile literature; Moon -- Exploration -- Juvenile literature; Mars (Planet) -- Exploration -- Juvenile literature; Outer space -- Exploration -- Juvenile literature; Mathematics; Space sciences -- Mathematics; Moon -- Exploration; Mars (Planet) -- Exploration; Outer space -- Exploration